Water stable isotopes (Î´2H and Î´18O) in the Yucatán Peninsula, Mexico - Cejudo, Eduardo; Acosta-González, Gilberto; Leal-Bautista, Rosa Maria; Estrada-Medina, Héctor (Tecnología y ciencias del agua, 2022)
The hydrogen and oxygen isotopic composition of water is a very important tool to estimate water balance, groundwater recharge, and evaporation. Stable water isotopes integrated with hydrogeological and dating tools have been used to increase our understanding of the distribution and amounts of renewable and non-renewable groundwater. Isotopic data from precipitation and groundwater are widely available in Mexico, though there is little information on the Yucatan Peninsula, an area heavily relying on groundwater for which current estimates of groundwater availability are uncertain. In this paper, we compiled published and unpublished Î´2H and Î´18O data on precipitation as well as ground- and soil waters to obtain a regional meteoric water line (RMWL) at the Peninsula level, expressed by the equation Î´2 H= 8.18 Î´18 O + 10.29 The current data set suggests that precipitation originates in convective systems, low-pressure events, frontal events, and re-cycled moisture. The evaporation lines from groundwater isotope data suggest a mix of water with different isotopic compositions, but also provide clues to recent rapid recharge from precipitation, likely from rain events of great intensity. We present a groundwater isoscape of the Yucatan Peninsula and finally address the potential use of isotope data for groundwater management.